Zagadnienie percepcji języka naturalnego w triadzie: język ojczysty – język globalny – język sąsiedni na przykładzie triady język polski – język angielski – język niemiecki w ujęciu ekolingwistycznym: próba typologii - Puppel, Stanisław; Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2018)
In the present article an attempt has been made to throw some light on the question of native language user awareness under conditions of long-term language contact in the particular conditions of the so-called ”soft invasion” of English and German as foreign languages upon the ‘core’ of the Polish linguistic community, whereby the Polish students, aged 20-30 years, who have been learning English and German as foreign languages in different institutions of higher learning in Poland, have been able to propose an appropriate rating of Polish, English and German in the framework: ‘native language – global language- neighbouring language’. The typology proposed herein, as a result of an analysis of a questionnaire addressed to the above defined group of subjects, is based on the notions of ‘language substratum’, ‘language adstratum’, and ‘language superstratum’ as reflecting the different degrees of language awareness based on the collective functioning of a number of selected parameters. In the present study, the parameters of ‘usefulness’, ‘betterness’, and ‘sustainability/maintenance’ have been used. It has been shown that, as a result of language contact defined above, different levels of awareness of the contacting languages may be established. Subsequently, an attempt at showing the different status of Polish, German and English in the afore mentioned group of subjects has been made and a number of conclusions, general and specific, have been drawn. In particular, it has been postulated that the overall mechanism of generating the different degrees of natural language awareness involves a (socially and individually) relevant process of joint perception and evaluation of the languages under generally long-term ”mild invasion” contact conditions, or, more precisely, the joint perception and evaluation of the sheaths surrounding the particular languages which collide with each other. Under these conditions, Polish has been found as a weakly superstratal language (i.e. with a single bent toward the substratal value of ‘usefulness’, German has been defined as a strong adstratal language (i.e. with a single bent toward the superstratal value of ‘sustainability’), while English has been defined as a uniformly superstratal language (i.e. with all the three parameters obtaining the highest value). The results thus obtained may serve as a basis for further discussions on the relevance of the notions of ‘local’ versus ‘global’ language.